Prevalence of metabolic syndrome and associated factors in an urban area of Bihar - Pravin, Kumar; Chandra, Prakash; Lal, Prabhat Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Metabolic syndrome is a conglomeration of physiological, biochemical and clinical abnormalities which include insulin resistance, hypertension and dyslipidemia and leads to increased risk of cardiovascular disorders, stroke and diabetes. Its prevalence ranges from 11-56% in India. Methods: The present study was community based cross sectional in nature conducted upon 344 adults above 18 years of age and living in the urban area. Cluster sampling was done for selection of respondents. Pretested proforma was used for data collection which contained questions related to sociodemographic profile of the study subjects, anthropometric measurements and results of biochemical investigations. Results: About one-fourth of the respondents were below 30 years of age. 52% were males. 32.8% were suffering from metabolic syndrome. Physical activity assessment revealed that 46.2% of them were having sedentary life style. 79.7% of them did not consume fruits and 82% of them did not consume vegetables as recommended.16% used tobacco in any form and 9.9% took alcohol. Lack of physical activity and less consumption of fruits & vegetables were significantly associated with metabolic syndrome. Conclusions: Metabolic syndrome was significantly associated with age, education, socioeconomic status, physical activity and consumption of fruits & vegetables.